Analysis of HIV/AIDS Response among Adolescents in Kendari City Southeast Sulawesi Province, Indonesia - Yulisti, Sry; Latoso, Rudi; Kusumajaya, Ida; Sari, Sitti Nurmayang; Tosepu, Ramadhan; Effendy, Devi Savitri; Susanty, Sri (Miracle Journal of Public Health, 2023)
A case HIV/AIDS remains a global public health problem, including in Indonesia. It is estimated that the wide variety of HIV/AIDS patients in Indonesia will continue to grow. Some of the strategic initiatives have been implemented to achieve the SDGs and target indicators. HIV/AIDS in young people HIV/AIDS PDP Kendari city hospitals and health centres work areas. This examination makes use of a qualitative technique mixed with a descriptive case observation. Information series techniques through interviews, observations and statistics (documentary research). HIV/AIDS strategy and control in Kendari city consists of promotion strategies (HIV/AIDS education for the community and key population groups), prevention strategies (prevention of infection and provision of HIV testing services), treatment strategies (HIV/AIDS treatment facilities, mitigation of the effects of HIV/AIDS). The development of strategies and efforts to combat HIV/AIDS in Kendari City is strongly influenced by partnerships with external agencies, cross-sectoral coordination and an increased role of civil society through AIDS treatment groups, political implementation approach groups, and the willingness of target groups to. follow the policy.